2013
DOI: 10.1007/s00198-013-2345-2
|View full text |Cite
|
Sign up to set email alerts
|

Poor histological healing of a femoral fracture following 12 months of oestrogen deficiency in rats

Abstract: Long-term ovariectomy has a deleterious effect on fracture healing in a rodent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…The OVX rat has been widely used as an estrogen-deficient model for the research study of post-menopausal bone loss (811,13,14,1820). In addition to bone loss and the deterioration of biomechanical properties, IVD degeneration is also observed in this model.…”
Section: Discussionmentioning
confidence: 99%
“…The OVX rat has been widely used as an estrogen-deficient model for the research study of post-menopausal bone loss (811,13,14,1820). In addition to bone loss and the deterioration of biomechanical properties, IVD degeneration is also observed in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies showed differences in bone healing involving less callus formation in the metaphyseal area with more endosteally bone healing than in the diaphysis during fracture healing [2,3,4,30]. Regarding the pathophysiology of osteoporotic bone, several reports suggest deviations in healing patterns in osteoporotic bone from the normal course in diaphyseal fracture model and drill-hole defects [31][32][33][34][35][36][37][38][39]. Metaphyseal fracture healing was addressed only with a couple of models, which studied either a small sized gap [4,18,22,[40][41][42] a drill-hole defect [9,[43][44][45][46] or partial osteotomy [1].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Many studies suggest differences in bone healing in osteoporotic vs. physiological bone status [32,35,36,37,39]. In a comparative study between ovariectomized (OVX) and sham-operated (SHAM) rats, provided with a 3 mm wedgeshaped fracture-defect in the metaphyseal area of the femur, histological and biomechanical differences could be constituted.…”
Section: Osteoporotic Bone Healingmentioning
confidence: 99%
“…Treatment of osteoporotic fractures, particularly of osteoporotic fractures with bone defects, remains a critical challenge. Accumulating evidence suggests that osteoporosis impairs healing of fractures . The mechanisms are complex, and are associated with weak osteogenesis and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that osteoporosis impairs healing of fractures. [2][3][4][5][6][7][8] The mechanisms are complex, and are associated with weak osteogenesis and angiogenesis. A reduction in the differentiation of mesenchymal stem cells (MSCs) into osteoblasts contributes to the impaired bone formation observed in osteoporosis.…”
Section: Introductionmentioning
confidence: 99%